Statistics for management - Levin, Richard I (Prentice-Hall, 1981)
16 chapters: Introduction; arring data to convey meaning: tables and graphs; summary measures of frequency distributions; measuring variability; probability I: Introductory ideas; probability II: distributions; sampling and sampling distributions;...